Familial hypercholesterolaemia: case studies, universal screening and novel mutations - Humphries, Steve (Henry Stewart Talks, 2023)
Familial hypercholesterolaemia case studies, NHS 5-year plan for FH, Universal screening for FH, Management of children with FH, Whole Exome Sequencing, Statins and their use in children, The 100,000 Genome Project